Chest wall mechanics and abdominal pressure during general anaesthesia in normal and obese individuals and in acute lung injury - Pelosi, Paolo; Lücke, Thomas; Rocco, Patricia R. M. (Current opinion in critical care, 2011)
PURPOSE OF REVIEW: This article discusses the methods available to evaluate chest wall mechanics and the relationship between intraabdominal pressure (IAP) and chest wall mechanics during general anaesthesia in normal and obese individuals, as well as in acute lung injury/acute respiratory distress syndrome. - RECENT FINDINGS: The interactions between the abdominal and thoracic compartments pose a specific challenge for intensive care physicians. IAP affects respiratory system, lung and chest wall elastance in an unpredictable way. Thus, transpulmonary pressure should be measured if IAP is more than 12 mmHg or if chest wall elastance is compromised for other reasons, even though the absolute values of pleural and transpulmonary pressures are not easily obtained at bedside. We suggest defining intraabdominal hypertension (IAH) as IAP at least 20 mmHg and abdominal compartment syndrome (ACS) as IAP at least 20 mmHg associated with failure of one or more organs, although further studies are required to confirm this hypothesis. Additionally, in the presence of IAH, controlled mechanical ventilation should be applied and positive end-expiratory pressure individually titrated. Prophylactic open abdomen should be considered in the presence of ACS. - SUMMARY: Increased IAP markedly affects respiratory function and complicates patient management. Frequent assessment of IAP is recommended.
Gesehen am 11.10.2022